ANALYSIS OF CALCULATION IN Mudharabah TO INCREASE REVENUE TRADERS IN BMT of ATI BENING GROBOGAN DISTRICT - Tida, Khusnamah; Kholisoh, Dr. Luluk; Nawarcono, SE., MM, Winanto (Accounting, 2010)
The existence of an existing conventional bank interest in the system prioritizes operasiolnalnya, while the Islamic Bank are not familiar with the term of interest but which is the term used for the results. Banking with sharing system designed terbinanya for unity in the risks and share the results of operations between the owner of the funds that keep their money in the bank, with the bank as manager funds and also the people who need funds that can be existed as borrower or the fund manager. With financing coupled with the guidance capital management and business to business productivity help to improve which in turn will affect the increased revenue traders small. This is the basis for the author to take the title "Analyst calculation Mudharabah to increase the income of traders in BMT Ati Bening Grobogan district”. The purpose of this study was to describe and analyze the effect of Mudharabah increased income traders in District Grobogan. The population of this study is the customer who received BMT Bening Ati Mudharabah, whose population amounted to all customers, the sample There are 100 (40 data can be processed) and the sampling technique using proportional cluster random sampling technique. The method of data collection yangdigunakan methods are questionnaires and documentation. Methods of data analysis used in this research is simple regression analysis of prediktor.Hasil research shows that by calculating the correlation coefficient between variables X and Y variables dipeoleh r r hits at 10.500 and table is 1.98, which means there was significant correlation between the increase of revenue Mudharabah small traders. From the simple regression equation obtained Y = 4.987 + 1.215 X, While hypothesis testing is performed with T test t hits obtained for10.500 which means that said that Ha is the influence of financing to increase merchant revenues Grobogan District "Acceptable". Based on the above conclusions, the authors present suggestions include the need for further research on the variables that affect increased revenue that the available job opportunities, skills and expertise, motivation and tenacity to work. Keywords: Mudharabah, increased revenue.